PENERAPAN GERAKAN BRAIN GYM UNTUK MELATIH FOKUS (STUDI KUALITATIF) DI TK AISYIYAH IX KOTA BENGKULU - alsa sabrianti (UIN Fatmawati Sukarno Bengkulu, 2026)
This research is motivated by the low focus ability of 4-5-year-old children during classroom learning. Children are often easily distracted, get bored quickly, pay little attention to teacher explanations, and are unable to maintain attention for long periods. This study aims to determine the application of Brain Gym movements in training the focus of 4-5-year-old children at Aisyiyah IX Kindergarten in Bengkulu City and to identify the supporting factors and obstacles encountered in its implementation. This study used a qualitative method with a descriptive approach. The research informants consisted of the principal and class teachers of the 4-5-year-old age group. Data collection techniques were conducted through observation, interviews, and documentation, while data analysis utilized data reduction, data presentation, and conclusion drawing.The results showed that before the implementation of Brain Gym, some children were only able to maintain focus for 10-15 minutes and were easily distracted during the lesson. The implementation of Brain Gym was carried out through planning, implementation, and evaluation stages using the Brain Buttons movement, the Cross Crawl movement, and the Owl movement. The results showed that the implementation of Brain Gym had a positive impact on children's focus. Children become more easily guided, calmer, more actively engaged in learning, better able to pay attention to teacher explanations, and can maintain attention for longer. Supporting factors for Brain Gym implementation include children's enthusiasm, teacher support, and simple movements. Challenges include children who are easily distracted, differences in ability to follow movements, and varying emotional states.